Books Completed or in Progress by Academy Members (Academy of Management Journal, 1964)
The article presents a list of books related to management. They include “The Managing of Organizations,” by Bertram M. Gross, “Scientific Management and Human Relations,” by Robert J. Daiute, and “International Enterprise in a Developing Economy,” by Claude McMillan, Richard Gonzales, and Leo Erickson.